2020
DOI: 10.3389/fmicb.2020.574137
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Suspected Probiotic Organisms in Preterm Infant Gut Microbiota Weeks After Probiotic Supplementation in the NICU

Abstract: Probiotics are becoming a prevalent supplement to prevent necrotizing enterocolitis in infants born preterm. However, little is known about the ability of these live bacterial supplements to colonize the gut or how they affect endogenous bacterial strains and the overall gut community. We capitalized on a natural experiment resulting from a policy change that introduced the use of probiotics to preterm infants in a single Neonatal Intensive Care Unit. We used amplicon sequence variants (ASVs) derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 53 publications
4
40
0
Order By: Relevance
“…However, our results suggest that Bifidobacterium persists beyond this time point, as the genus was present in all 23 infants with samples collected > 36-weeks gestation. This supports previous studies that have observed long-term probiotic-species colonization, at least with Bifidobacterium ( 14 , 83 ). As moderate to late-preterm infants are at a lower risk of acute disorders than those born very-preterm ( 34 , 35 ), long-term benefits provided through probiotic-treatment may be more significant for the moderate to late-preterm demographic.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results suggest that Bifidobacterium persists beyond this time point, as the genus was present in all 23 infants with samples collected > 36-weeks gestation. This supports previous studies that have observed long-term probiotic-species colonization, at least with Bifidobacterium ( 14 , 83 ). As moderate to late-preterm infants are at a lower risk of acute disorders than those born very-preterm ( 34 , 35 ), long-term benefits provided through probiotic-treatment may be more significant for the moderate to late-preterm demographic.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that infant-type HRB are more effective colonizers of the infant gut. Consistent with this finding, it was shown the persistent colonization of probiotic strains of B. longum , B. bifidum , and B. breve up to 5 months after supplementation of commercially probiotics containing these Bifidobacterium strains and Lactobacillus rhamnosus strain in preterm infants ( Yousuf et al, 2020 ). Another study also indicated that the administration of B. longum subsp.…”
Section: Discussionsupporting
confidence: 55%
“…Probiotics supplementation is a promising approach to improve dysbiosis and prevent gut microbiota-associated diseases in LBW infants. However, it is unclear whether the microbial components in probiotic treatments can persist in the gut during early life, although some studies indicated the potential for some probiotics ( Frese et al, 2017 ; Alcon-Giner et al, 2020 ; Yousuf et al, 2020 ) as described below. This study found the colonization of B. breve M-16V in the intestinal tract of most LBW infants for at least several weeks following cessation of its administration as a probiotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infantis, B. lactis and S. thermophilus exist between probiotic and control infants. Finally, the detection of the probiotic species in samples collected prior to supplementation could indicate some cross-colonization took place while the infants were in the neonatal unit, which has previously been reported [20,[28][29][30].…”
Section: Discussionmentioning
confidence: 76%